The land of the spring dragon ebook - West, Tracey (Dragon Masters, 2019)
Drake travels to a secret fairy world to save the Kingdom of Bracken! Pick a book. Grow a Reader!This series is part of Scholastic's early chapter book line, Branches, aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow!Drake's kingdom is in trouble — a terrible earthquake has destroyed Bracken's crops! A magical Spring Dragon has the power to save the kingdom and regrow the crops, but he lives deep inside a secret fairy world. To find the Spring Dragon, Drake must pass a series of tests given by a Dragon Master named Breen. But the fairy world is full of confusing tricks and mysterious riddles! Can Drake save his kingdom?